2007
DOI: 10.1103/physrevb.76.094112
|View full text |Cite
|
Sign up to set email alerts
|

Thermally activated motion of dislocations in fields of obstacles: The effect of obstacle distribution

Abstract: The thermally activated motion of dislocations across fields of obstacles distributed at random and in a correlated manner, in separate models, is studied by means of computer simulations. The strain rate sensitivity and strength are evaluated in terms of the obstacle strength, temperature and applied shear stress. Above a threshold stress, the dislocation motion undergoes a transition from smooth to jerky, i.e. obstacles are overcome in a correlated manner at high stresses, while at low stresses they are over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…[3,4] The model details are presented in the cited references; here we only review its main features. The dislocations are represented as flexible strings of line tension C ¼ 1=2Gb 2 (G is the shear modulus and b is the Burgers vector length).…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] The model details are presented in the cited references; here we only review its main features. The dislocations are represented as flexible strings of line tension C ¼ 1=2Gb 2 (G is the shear modulus and b is the Burgers vector length).…”
Section: Modelingmentioning
confidence: 99%
“…This adds to previous numerical studies of the way the type of obstacles to dislocation motion control the flow stress and the strain rate sensitivity in single glide. [3,4] In these references, it was shown that if one starts with a population of weak obstacles and adds a small fraction of strong (more athermal) obstacles, the flow stress changes little, but the strain rate sensitivity decreases significantly. Hence, indirectly, the present experimental results shed light on the nature of precipitation in these alloys, and in particular, on the fact that precipitates (probably of slightly different nature) interact with dislocations differently in Mg-rich and Si-rich Al alloys.…”
Section: Introductionmentioning
confidence: 97%
“…associated with local line length and curvature. However, Γ actually consists of contributions from both the local increase in dislocation length and the longer-range interactions among all segments of the dislocation line, which leads to a ln(L) scaling with line length L. A simple approximation, Γ ≈ 1 2 µb 2 [10,11,[26][27][28][29][30][31][32], where µ is the shear modulus and b the Burgers vector was originally proposed over half a century ago [30,31]. A more nuanced model accounts for the long-range interactions by modifying the prefactor of 1/2 and adding the ln(L) scaling that emerges from elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Dislocations are pinned by various types of obstacles, with applied stress and thermal activation allowing the dislocations to move through a field of obstacles [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Increasingly sophisticated models are guiding the understanding of these processes, and their consequences on observable/measurable phenomena [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary numerical work was done by Morris and Klahn. [42] Recent work within one set of models for thermal activation has been carried out by Picu et al, [21,43] showing regimes of complicated strengthening and strain rate sensitivity at finite temperature. With a clear picture of the applicability of linear and geometric rules for athermal (zero temperature) strengthening due to multiple obstacles, and the transition between these two regimes, we are now carrying out a more complete study of thermally activated flow and will report on the outcomes in the future.…”
Section: Discussion and Summarymentioning
confidence: 99%